(untitled) (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Between 2024 and 2025, IPIAP, in partnership with TNC, conducted studies in the Napo River and its tributaries, revealing a remarkable diversity of commercial fish. A total of 40 species of bony fishes were identified, belonging to 21 families and nine orders. The most representative family was Pimelodidae, with 10 species. Regarding their conservation status, the majority 83% of the species are classified as Least Concern according to the IUCN, with none currently listed in a threatened category. Fishing activity in the area is artisanal, with 77 fishing grounds recorded. Fishers use seven types of fishing gear, including gillnets, cast nets, hand lines, and harpoons. In order to ensure the long-term sustainability of these resources, reproductive monitoring of the main species is being carried out, which will support the development of recommendations for appropriate fisheries management in the Ecuadorian Amazon.